Refleksi Arsitektur Vernakular Pada Bangunan Bantayo Pobo'ide Di Kabupaten Gorontalo - Eka, Rahmawati; Supu , Adam; Dwi Arini , Lutfiah (JARI: Journal of Architecture, Research and Innovation, 2025)
The Bantayo Poboide traditional house is an important symbol of Gorontalo culture. In the social structure and traditional government of the Gorontalo people, this house is not only used as a residence or meeting hall, but also as a representation of noble values ​​that are inherited from generation to generation. The name Bantayo Poboide comes from two words in the Gorontalo language, namely "bantayo" which means building or house, and "poboide" which means a place for deliberation. Architecturally, Bantayo Poboide is built in the style of a stilt house, made entirely of wood with a structure that reflects traditional philosophy. The purpose of this study is to identify the elements of vernacular architecture in Bandayo poboide. The study was conducted at the Bantayo Poboide Traditional House, Kayu Bulan Village, Limboto District, Gorontalo Regency. This study uses a qualitative method, data collection techniques are carried out by means of observation, interviews, and documentation. Bantayo Poboide is a real example of Gorontalo vernacular architecture that is not only adaptive to the environment and climate, but also reflects the cultural, social, and spiritual values ​​of its people. Its wood-based architecture, gable roofs, and stilt houses are evidence of the harmony between humans and nature. The symbolism and structure of the building make Bantayo Poboide a very valuable cultural heritage.